The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/s004360050106
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two isolates of Trypanosoma cruzi obtained from the patient Berenice, the first human case of Chagas' disease described by Carlos Chagas in 1909

Abstract: Two isolates of Trypanosoma cruzi were obtained from the patient Berenice, the first human case of Chagas' disease (Chagas 1909), when she was 55 and 71 years old, respectively. The isolates were characterized on the basis of their epimastigote-trypomastigote differentiation in liquid media and of the electrophoretic pattern of EcoR1 digestion products of kinetoplast DNA (k-DNA) minicircles (schizodeme) and isoenzyme patterns (zymodeme). Clear differences were found between the isolates, suggesting the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…These findings could be related to the reduction of genetic complexity in T. cruzi strains isolated from chronic chagasic patients (Morel et al 1980;Tibayrenc and Ayala 1988;Oliveira et al 1997;Macedo et al 1992). Another explanation should be due to the fact that in the exact moment of parasite isolation from the host, a particular population could predominate over others, since in the T. cruzi life cycle, bloodstream trypomastigotes release does not occur by circadian rhythm (Lana et al 1996). Recently, comparative data analysis of the RAPD and isoenzyme profiles has shown two distinct groups of T. cruzi isolated from chronically infected dogs with Berenice-78 strain after long-term infection (Veloso et al 2005).…”
Section: Discussionmentioning
confidence: 83%
“…These findings could be related to the reduction of genetic complexity in T. cruzi strains isolated from chronic chagasic patients (Morel et al 1980;Tibayrenc and Ayala 1988;Oliveira et al 1997;Macedo et al 1992). Another explanation should be due to the fact that in the exact moment of parasite isolation from the host, a particular population could predominate over others, since in the T. cruzi life cycle, bloodstream trypomastigotes release does not occur by circadian rhythm (Lana et al 1996). Recently, comparative data analysis of the RAPD and isoenzyme profiles has shown two distinct groups of T. cruzi isolated from chronically infected dogs with Berenice-78 strain after long-term infection (Veloso et al 2005).…”
Section: Discussionmentioning
confidence: 83%
“…Although isolated from the same patient, these two strains displayed several biological and molecular differences [19], [31][33]. However, because only two alleles were detected for the molecular markers used in their characterization, both strains were initially supposed to be monoclonal [34].…”
Section: Resultsmentioning
confidence: 99%
“…He gave a detailed clinical description of the acute phase of the disease and linked the infection with some chronic symptoms of the illness which was remarkable considering that the chronic phase of American trypanosomiasis usually appears decades after the first inoculation with T. cruzi (reviewed in [46]). Interestingly, his first patient Berenice never developed determinate chronic Chagas disease and died at the age 73 years on unrelated causes [47]. However, she was infected with T. cruzi for her whole life as was confirmed by the isolation of parasites when she was 55 and 71 years old [47].…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, his first patient Berenice never developed determinate chronic Chagas disease and died at the age 73 years on unrelated causes [47]. However, she was infected with T. cruzi for her whole life as was confirmed by the isolation of parasites when she was 55 and 71 years old [47]. In 1912, Chagas reported that he had detected T. cruzi in an armadillo and thus found the first sylvatic reservoir host [48].…”
Section: Reviewmentioning
confidence: 99%